The Formation of Plato's Theory of Ideas - Раджапов Азиз Анарбаевич (Scientific Trends, 2025)
The article examines the process of formation of the theory of ideas in Plato's philosophy. The author analyzes the intellectual origins of the concept associated with the teachings of Heraclitus, Parmenides and Socrates, as well as the main stages of the development of the doctrine in Plato's dialogues Philosophy.
Keywords: Plato, ideas, eidos, metaphysics, Socrates, Heraclitus, Parmenides, cognition, ancient philosophy.